The Use of Project Time Management Processes and the Schedule Performance of Construction Projects in Mexico. (15th October 2015) - Solís-Carcaño, Rómel G.; Corona-Suárez, Gilberto A.; García-Ibarra, Aldo J.
Abstract : Delays have been frequently reported as the cause of several conflicts that affect the different parties involved in construction projects. Project Time Management (PTM) includes a number of planning and controlling processes that are recommended for complying with requirements related to project time. The study reported in this paper aimed at assessing the use of PTM processes and its relation with project schedule performance (i.e., timely completion). Seven PTM processes and seventy-seven tasks associated with them were identified from the literature that is globally relevant to project management. The study included the assessment of fourteen school construction projects executed by a public agency in the Yucatan Peninsula, Mexico. These projects were monitored during the construction phase in order to measure two different variables: the use of processes related to PTM (i.e., schedule planning and controlling processes) and the project schedule performance. For each of these projects a Use Index was obtained for assessing the first variable, while the Schedule Performance Index and the Schedule Variance were computed to assess the second one. The results demonstrated there is statistical dependence between these two variables. Most of the projects that attained timely completion also made a greater use of the PTM processes.